Serum biochemical indicators in rats of different ages after replacing femoral metaphysis defects with allogeneic bone implants saturated with mesenchymal stem cells - Vorontsov, P. M.; Korzh, M. O.; Leontieva, F. S.; Tuliakov, V. O. (Zaporozhye Medical Journal, 2023)
The aim of the study: to evaluate the course of metabolic processes after replacing femoral metaphysis defects with allogeneic bone implants saturated with allogeneic mesenchymal stem cells (MSCs) based on the analysis of serum biochemical indicators of connective tissue metabolism in laboratory rats. Material and methods. A critical-sized transcortical femoral defect model in the femur metaphysis of white rats was used. Blood serum concentrations of glycoproteins, total chondroitin sulfates, total protein and calcium, alkaline and acid phosphatase activity were measured. Results. On the 28th day, in 3-month-old animals with MSC, in comparison with the data of rats without MSC, clear signs of connective tissue formation and bone resorption activity were observed, as evidenced by an increase in serum chondroitin sulfates and acid phosphatase activity. On the 90th day, this group of rats under the influence of MSCs showed signs of decreased bone tissue formation with lower serum activity of alkaline phosphatase. In 3-month-old rats with MSC, signs of the inflammatory process chronization with higher serum concentrations of glycoproteins were detected on the 90th day of the experiment in comparison with data from animals without MSC. In 12-month-old rats with MSCs, signs of bone resorption were documented on the 14th day, which were manifested by a higher serum activity of acid phosphatase with less formation of connective tissue and lower concentrations of chondroitin sulfates. On the 28th day, the effect of MSCs in 12-month-old animals was manifested in the form of a slowdown in bone formation with a decrease in alkaline phosphatase activity. On the 90th day, the connective tissue formation was activated with higher concentrations of chondroitin sulfates in these animals. Conclusions. The studied biochemical indicators in 3-month-old animals showed greater lability. The regeneration phases were faster in 3-month-old animals as well as in animals with alloimplants without MSCs. Injections of allogeneic MSCs together with an allograft immediately after a bone damage, regardless of age, caused signs of bone formation slowing and excessive formation of connective tissue, therefore, the combination of allogeneic MSCs with an allogeneic bone implant is not advisable to use in fresh fractures.